A New Worldview of Soils. Issue 6 (24th October 2014) - Lin, Henry
Abstract : In the spectrum of things in nature that range from nonliving to living, soils fall right in the middle—functioning as the bridge between the biotic and the abiotic worlds and possessing enormous internal power as the nurturing ground for life. A fundamental shift is needed to understand and manage complex, semi‐living soil systems. After the Newtonian and Darwinian worldviews, a third worldview is emerging that integrates living and nonliving entities as well as space and time cultures. This new worldview emphasizes the interwoven nature of conservation and evolution, the intimate link between internal organization and system function, the system between extremes, and the unprecedented anthropogenic impacts. A new kind of physics is suggested for enhanced understanding of soil complexity, including (i) the modification of Newton's three laws of motion, (ii) the internal organization (rather than externality) of soils in response to perturbations, and (iii) the medium number syndrome (systems too complex for classical analytics and too organized for statistical treatment). Soils are a great subject for the study of complexity and sustainability, where non‐closed cycles and irreversible thermodynamics prevail. However, modern soil vulnerability to global change and anthropogenic threats is unprecedented. If current land use and hazard trends are not adjusted, we may run the risk of losing the ground for sustainability. We need innovative investigations toward building better human systems that are in harmony with functional soils and ecosystems.